2013
DOI: 10.1038/ncomms2510
|View full text |Cite
|
Sign up to set email alerts
|

Surface-passivated GaAsP single-nanowire solar cells exceeding 10% efficiency grown on silicon

Abstract: Continued development of high-efficiency multi-junction solar cells requires growth of latticemismatched materials. Today, the need for lattice matching both restricts the bandgap combinations available for multi-junctions solar cells and prohibits monolithic integration of high-efficiency III-V materials with low-cost silicon solar cells. The use of III-V nanowires is the only known method for circumventing this lattice-matching constraint, and therefore it is necessary to develop growth of nanowires with ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
227
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(231 citation statements)
references
References 24 publications
2
227
0
1
Order By: Relevance
“…Furthermore, GaAs nanowire-based solar cells can be grown on Si, easily resulting in a dual-junction device [7]. Proof-of-concept radial p-i-n GaAs nanowire solar cells have been demonstrated in the past [8][9][10][11][12][13]. Recently, it has been shown that the achievement of high efficiencies can only be obtained after the accurate design of the individual junction, the nanowire diameter, and density so that light absorption and conversion are maximized [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GaAs nanowire-based solar cells can be grown on Si, easily resulting in a dual-junction device [7]. Proof-of-concept radial p-i-n GaAs nanowire solar cells have been demonstrated in the past [8][9][10][11][12][13]. Recently, it has been shown that the achievement of high efficiencies can only be obtained after the accurate design of the individual junction, the nanowire diameter, and density so that light absorption and conversion are maximized [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Holm et al fabricated solar cells from broken GaAsP NWs that were grown on Si substrates [200]. By using an InGaP passivation layer on the GaAsP NWs, the efficiency of the best cell was reported to improve by 50%, from 6.8% in unpassivated NWs to 10.2% in passivated NWs.…”
Section: Refinement Of Growth Conditions For Improved Device Performamentioning
confidence: 99%
“…-The efficiency of the solar cell has been reported to improve by using a passivation layer [32,200]. Holm et al fabricated solar cells from broken GaAsP NWs that were grown on Si substrates [200].…”
Section: Refinement Of Growth Conditions For Improved Device Performamentioning
confidence: 99%
“…While SiO 2 offers remarkable surface passivation properties for silicon 10 , a comparable solution for III-V semiconductors remains absent. On the other hand, low-defect single-crystal nanostructures can be grown with atomically flat surfaces and in situ surface passivation via higher band gap cladding layers 11,12 , which have historically proven to provide the best passivation for III-V materials. With tiny footprints, nanostructures incur minimal real estate cost while offering full photonic functionality.…”
mentioning
confidence: 99%